FORMATION OF INFORMATION AND COMMUNICATION COMPETENCE OF FUTURE PHYSICAL REHABILITATION SPECIALISTS - Bismak, Olena (Educological discourse, 2017)
It is known that the main direction of the physical rehabilitation development in Ukraine is compliance with international standards for the training of specialists in this profile. One of the main criteria a physical therapist is evaluated are professional competences that are differed in content but consistent to the general direction proclaimed by the World Confederation of Physical Therapy. Increasing the professional competence of health professionals around the world is defined as the most important factor in reforming the health care system. Along with the general requirements for a physical therapist, which could satisfy the needs of both the individual and the society as a whole, the requirements for professional education in higher education institutions are growing. One of the priority directions of the education development in the transition to an information society is the use of computers and information systems in universities. The content, essence and features of the information and communication competence of future physical therapists formation are disclosed in the article. It is noted the identification of information and communication competence as a separate component of the physical therapists professional competence is due to the active using of information and communication technologies in all spheres of human activity, including in health care system. The author notes the essence of the physical therapist information competence consists the ability to obtain knowledge about the ways of processing, transferring, storing and presenting professional information using computer technology. The article emphasizes that communication competence is also very important for a physical therapist because a specialist in the field of physical rehabilitation has to communicate directly with different people in the performance of his professional duties, using verbal and non-verbal methods of communication, to be able to establish contact, listen, build a conversation with the patient.